Therapeutic Alliance in Substance Dependence Treatment: HAq-II Comparisons between Social Workers and Nurses. Issue 47 (4th March 2021) - Fendrich, Michael; Becker, Jessica
Abstract: As social workers and nurses comprise much of the substance dependence treatment team, it is critical to evaluate how well they perform in a context where they bring different professional orientations and perform different treatment roles. The therapeutic alliance (TA) is one clinical outcome indicator that is potentially predictive of client engagement and retention, two prerequisites for successful treatment. TA in substance dependence treatment has been measured using the Revised Helping Alliance Questionnaire (HAq-II), a 19-item likert-type measure assessing clients' perceived "therapeutic alliance" with the therapists who are treating them. Through secondary analysis of the 2006-2010 Addiction Health Evaluation and Disease (AHEAD) Management Study, the authors examined alcohol or other drug-dependent participants (N = 60) who completed the HAq-II for the social workers and nurses. Findings reveal that social workers' scores were significantly higher than scores for the nurses. On average, social workers received a score 8.5 points higher than nurses (p < 0.001). Implications for the participation of social workers and other health professionals in interprofessional addiction treatment teams and directions for future research are discussed.